The significance of critical incidents and voice to identity and agency. Issue 6 (17th August 2016) - Sisson, Jamie Huff
Abstract: Human agency is significant to the understanding of professional identities and actions. It is through human agency that individuals can become powerful in changing or authoring their own identities. Stemming from a larger narrative inquiry focused on understanding the professional identities of public preschool teachers, this paper draws on cultural models theory to explore identity, agency and professional practice through the lived stories of CeCe, an African-American public preschool teacher from the United States. Findings demonstrate the influence of CeCe's lived experiences to her developing sense of human agency and highlight the importance of critical incidents and voice to identity and human agency.